Kesesuaian Lahan Kawasan Permukiman Berdasarkan Kemampuan Lahan BWK II Kota Semarang - Suryani, Tia Adelia; Adharina, Nabilla Dina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Limited land followed by high population growth and urban development will be a problem for many sectors, especially the environmental aspect. Thus, urban development must be directed. The development of a good residential area is one that is in accordance with the development area. BWK II Semarang City is predicted to experience growth in 2031 up to 24.41%, even though the majority of land use is in the form of residential areas. The development of BWK II which tends to be rapid and followed by population growth is feared to increase the need for settlements. Land capability is considered to be one method to analyze which areas can still be developed. The purpose of this study is to determine the suitability of land capability in the BWK II residential area of ​​Semarang City. This study uses a quantitative research method with a spatial approach. The settlement area was analyzed by land capability using 9 Land Capability Units (LCAP) which include: Morphological LCAP, Workability LCAP, Slope Stability LCAP, Foundation Stability LCAP, Water Availability LCAP, Erosion LCAP, Drainage LCAP, Waste Disposal LCAP, and Natural Disaster LCAP. The results of the land capability were overlaid with the settlement area. The results showed that 97% of the settlement area was still in accordance with the development area and 3% of the settlement area in BWK II was not in accordance with the development area, including in parts of Karanganyar Gunung Village, Bendan Ngisor Village, and Gajah Mungkur Village.